Strategy for Revitalization of the Senggigi Tourism Area Based on Sustainable Tourism Development in West Lombok Regency - Fajriah, Alifatul; Sudiartha, Handry; Basuki, Prayitno (Empiricism Journal, 2026)
Senggigi Tourism Area, as the pioneering tourism destination on Lombok Island, has experienced a decline in competitiveness due to infrastructure degradation, deterioration of the coastal environment, changing tourist preferences, and increasing competition from emerging destinations. These challenges highlight the need for a revitalization strategy that not only focuses on physical improvements but also integrates the principles of Sustainable Tourism Development (STD) to ensure long-term destination sustainability. This study employs a qualitative approach with a case study design, utilizing SWOT analysis through the development of IFAS and EFAS matrices to identify internal and external factors affecting destination revitalization. This study aims to analyze the internal and external factors influencing the revitalization of the Senggigi Tourism Area and to formulate revitalization strategies based on Sustainable Tourism Development. This research employed a qualitative approach using a case study design. Data were collected through field observations, in-depth interviews with stakeholders representing the pentahelix elements, and document analysis. Data were analyzed using SWOT analysis through the development of IFAS and EFAS matrices to identify the strengths, weaknesses, opportunities, and threats affecting the destination’s development. The findings reveal that Senggigi possesses several strengths, including a strong destination image, attractive natural and cultural resources, adequate tourism facilities, and government policy support. However, the area also faces significant challenges, such as aging infrastructure, coastal environmental degradation, limited tourism product innovation, and weak stakeholder collaboration. The IFAS and EFAS analysis results show scores of 2.58 and 2.72 respectively, indicating a relatively strong strategic position for revitalization. Based on the SWOT analysis, the recommended revitalization strategies include the development of green tourism and smart tourism initiatives, environmentally friendly infrastructure revitalization, coastal conservation programs, diversification of tourism products based on local culture and the creative economy, and the strengthening of collaborative governance through the establishment of a Destination Management Organization (DMO). This research contributes theoretically to the development of literature on mature tourist destination revitalization, while practically providing strategic recommendations for local governments, destination managers, and stakeholders in realizing sustainable and competitive coastal tourism destination management. These strategies are expected to enhance the competitiveness and sustainability of the Senggigi Tourism Area in the long term.